Pengaruh Kesulitan Keuangan, Risiko Litigasi, dan Biaya Politik terhadap Konservatisme Akuntansi - Wiecandy, Nicko; Khairunnisa, Khairunnisa (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
Conservatism is a precautionary measure that is implemented by recognizing the costs that may be incurred immediately and not immediately recognizing revenue even though it is likely to have a large objective aimed at avoiding uncertainty in the company. This study aims to determine the effect of Financial Difficulties, Litigation Risk, and Political Cost to Accounting Conservatism. The population of this research is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The sampling technique in this study used purposive sampling and obtained 10 (ten) companies in food and beverage companies with an observation period of 5 (five) years so that in this study obtained 50 observational data. The method used in this research is panel data regression analysis using EVIEWS 10 software. The results of the study indicate that Financial Difficulties, Litigation Risks, and Political Cost simultaneously influence Accounting Conservatism. Partially, political cost has a positive effect on accounting conservatism, while financial difficulties and litigation risk do not affect accounting conservatism. Keywords: Accounting Conservatism, Financial Distress, Litigation Risk, Political Cost